Interrelation between microstructure and optical properties of erbium-doped nanocrystalline thin films - Losurdo, M. (2003)
Nanocrystalline silicon thin films codoped with erbium, oxygen and hydrogen have been deposited by co-sputtering of Er and Si. Films with different crystallinity, crystallite size and oxygen content have been obtained in order to investigate the effect of the microstructure on the photoluminescence properties. The correlation between the optical properties and microstructural parameters of the films is investigated by spectroscopic ellipsometry. PL response of the discussed structures covers both the visible wavelength range (a crystallite size-dependent photoluminescence detected for 5–6 nm sized nanocrystals embedded in a SiO matrix) and near IR range at 1.54 microm (Er-related PL dominating in the films with 1–3 nm sized Si nanocrystals embedded in a-Si:H). It is demonstrated that the different PL properties can be also discriminated on the basis of ellipsometric spectra.